Does a standardised exercise protocol incorporating a cognitive task provoke postconcussion-like symptoms in healthy individuals?. Issue 3 (May 2015) - Lee, Hopin; Sullivan, S. John; Schneiders, Anthony G.
Abstract Objectives To explore whether an exercise protocol, alone and in combination with two selected cognitive tasks related to working memory, provokes postconcussion-like symptoms in healthy individuals. Design Prospective single cohort semi-randomised crossover repeated measures (time × condition) design. Methods 36 healthy individuals completed three submaximal exercise protocol conditions, namely: exercise alone, exercise with the paced auditory serial addition task, and exercise with Tetris. Self-reported symptoms were measured before exercise and 1-min and 15-min after the cessation of each exercise protocol using the Sports Concussion Assessment Tool 2-Postconcussion symptoms scale. Results Analysis of variance indicated a significant increase in symptom scores over time (p < 0.001), but no effect between conditions (p = 0.371) or a significant time × condition interaction (p = 0.444). Conclusions The combination of working memory tasks and a symptom provoking submaximal exercise protocol did not have an additional effect on the provocation of self-reported symptoms in healthy individuals. Furthermore, the two distinct methods of cognitive load delivery, controlled (paced auditory serial addition task) and pragmatic (Tetris), did not lead to a differential symptom response. These findings provide an initial insight into the scientific foundations for the symptom provocation model that is integral to the currently accepted clinical postconcussion return-to-play protocol.